The mitochondrial protease OMA1 acts as a metabolic safeguard upon nuclear DNA damage - Pablo Rivera-Mejías; Álvaro Jesús Narbona-Pérez; Lidwina Hasberg; Lara Kroczek; Amir Bahat; Steffen Lawo; Kat Folz-Donahue; Anna-Lena Schumacher; Sofia Ahola; Fiona Carola Mayer; Patrick Giavalisco; Hendrik Nolte; et al. (Cell Reports, 2023)
Summary: The metabolic plasticity of mitochondria ensures cell development, differentiation, and survival. The peptidase OMA1 regulates mitochondrial morphology via OPA1 and stress signaling via DELE1 and orchestrates tumorigenesis and cell survival in a cell- and tissue-specific manner. Here, we use unbiased systems-based approaches to show that OMA1-dependent cell survival depends on metabolic cues. A metabolism-focused CRISPR screen combined with an integrated analysis of human gene expression data found that OMA1 protects against DNA damage. Nucleotide deficiencies induced by chemotherapeutic agents promote p53-dependent apoptosis of cells lacking OMA1. The protective effect of OMA1 does not depend on OMA1 activation or OMA1-mediated OPA1 and DELE1 processing. OMA1-deficient cells show reduced glycolysis and accumulate oxidative phosphorylation (OXPHOS) proteins upon DNA damage. OXPHOS inhibition restores glycolysis and confers resistance against DNA damage. Thus, OMA1 dictates the balance between cell death and survival through the control of glucose metabolism, shedding light on its role in cancerogenesis.